Influência da temperatura de armazenamento nas características físico-químicas e nos teores de aminas bioativas em ovos - Giuliana Elisa de Oliveira (2006)
Influence of storage temperature on the physico-chemical characteristics and levels of bioactive amines in eggs. The objective of this study was to investigate the influence of storage temperature on the physico-chemical characteristics and the levels of bioative amines in eggs. Eggs from Dekalb hens were stored at 6 ± 1 ºC and 25 ± 1ºC during 50 and 30 days, respectively. The fresh eggs were characterized with regard to volume; superficial area; density; egg, egg white and yolk weight; thickness and percentage of shell; height of the egg white; Haugh unities; resistance to fracture the egg shell; pH of the egg white; total solids; total volatile bases (TVB); and bioactiveamines. In fresh eggs TVB were not detected. Only spermidine was detected in the yolk. In the egg White a nonidentified amine was detected. During storage, there was weigth loss of the egg and of the egg white, and an increase in the weight of the yolk. The height of the egg white and the Haugh unities decreased whereas the total solidsand the pH increased in the egg white. The total solids of the yolk decreased in eggs stored at 6 ± 1 ºC. The force to fracture the shell and the deformation increased in eggs stored at 6 ± 1 ºC. There was formation of agmatine and putrescine in the yolk at 40and 15 days of storage at 6 ± 1 ºC and 25 ± 1 ºC, respectively. At this time, the totallevels of amines in the yolk exceeded 1.0 mg/kg. This value can be used as a limit, above which the egg would be of poor quality.